Removal of cadmium from contaminated soil using iron (III) oxide nanoparticles stabilized with polyacrylic acid - Mohamadiun, Malihe; Dahrazma, Behnaz; Saghravani, Seyed Fazlolah; Khodadadi Darban, Ahmad (Journal of Environmental Engineering and Landscape Management, 2018)
The aim of this study is to evaluate the effect of Fe3O4 nanoparticle, stabilized with polyacrylic acid on cadmium removal from the contaminated soils. To investigate the effect of important parameters, including nanoparticle concentration, pH, contact time, and the ratio of contaminated soil mass to nanofluid volume, several batch tests were performed. The maximum removal rate (100%) of cadmium was obtained in the following conditions: nanofluid concentration = 500 ppm, pH = 6.5, contact time = 24 hr and the ratio of contaminated soil mass (gr) to nanofluid volume (mL) = 1:150. Results of selective sequential extraction tests showed that the distribution of cadmium in different fractions of the soil was carbonates, oxides and hydroxides, residual fraction, exchangeable, and organic matter respectively. The tendency of nanoparticles for removal of Cd2+ from the soil fractions was in the order of: exchangeable > carbonates > oxides and hydroxides > organic matter > residual.